Walking Our Evidence-Based Talk: The Case of Leadership Development in Business Schools. (February 2022) - Leroy, Hannes L.; Anisman-Razin, Moran; Avolio, Bruce J.; Bresman, Henrik; Stuart Bunderson, J.; Burris, Ethan R.; Claeys, Johannes; Detert, James R.; Dragoni, Lisa; Giessner, Steffen R.; Kniffin, Kevin M.; Kolditz, Thomas; et al.
Academics have lamented that practitioners do not always adopt scientific evidence in practice, yet while academics preach evidence-based management (EBM), they do not always practice it. This paper extends prior literature on difficulties to engage in EBM with insights from behavioral integrity (i.e., the study of what makes individuals and collectives walk their talk). We focus on leader development, widely used but often critiqued for lacking evidence. Analyzing 60 interviews with academic directors of leadership centers at top business schools, we find that the selection of programs does not always align with scientific recommendations nor do schools always engage in high-quality program evaluation. Respondents further indicated a wide variety of challenges that help explain the disconnect between business schools claiming A but practicing B. Behavioral Integrity theory would argue these difficulties are rooted in the lack of an individually owned and collectively endorsed identity, an identity of an evidence-based leader developer (EBLD). A closer inspection of our data confirmed that the lack of a clear and salient EBLD identity makes it difficult for academics to walk their evidence-based leader development talk. We discuss how these findings can help facilitate more evidence-based leader development in an academic context.